Marseilleviruses: An Update in 2021 - Sahmi-Bounsiar, Dehia; Rolland, Clara; Aherfi, Sarah; Boudjemaa, Hadjer; Levasseur, Anthony; La Scola, Bernard; Colson, Philippe (Frontiers in Microbiology, 2021)
The family Marseilleviridae was the second family of giant viruses that was described in 2013, after the family Mimiviridae. Marseillevirus marseillevirus, isolated in 2007 by coculture on Acanthamoeba polyphaga, is the prototype member of this family. Afterwards, the worldwide distribution of marseilleviruses was revealed through their isolation from samples of various types and sources. Thus, 62 were isolated from environmental water, one from soil, one from a dipteran, one from mussels, and two from asymptomatic humans, which led to the description of 67 marseillevirus isolates, including 21 by the IHU Méditerranée Infection in France. Recently, five marseillevirus genomes were assembled from deep sea sediment in Norway. Isolated marseilleviruses have 250 nm long icosahedral capsids and 348-404 kilobase long mosaic genomes that encode 386-545 predicted proteins. Comparative genomic analyses indicate that the family Marseilleviridae includes five lineages and possesses a pangenome composed of 3,082 clusters of genes. The detection of marseilleviruses in both symptomatic and asymptomatic humans in stool, blood and lymph nodes, and an up-to-30-day persistence of marseillevirus in rats and mice, raise questions concerning their possible clinical significance that are still under investigation.